2014
DOI: 10.5799/ahinjs.02.2014.01.0121
|View full text |Cite
|
Sign up to set email alerts
|

Bipolaris spicifera : An unusual cause of non-healing cutaneous ulcers in a patient with diabetes and alcohol abuse

Abstract: This is a case report of Bipolaris spicifera, a dematiaceous fungus commonly found in soil and as a plant pathogen, isolated from culture of the lesions and from an excisional biopsy specimen in a patient with diabetes and alcohol abuse. This case highlights the importance of considering Bipolaris as a differential diagnosis in patients with cutaneous lesions and the need for vigorous management for complete cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Later, based on spore morphology and sporulation studies, group I isolates were identified as B. sorokiniana isolates with olive green to brown oblong conidia with prominent scar at the base, having dimensions in the range of 60–120 μm × 15–20 μm and 3–9 septa ( Aggarwal et al, 2009 ; Acharya et al, 2011 ; Devi et al, 2021 ). Group II isolates were further subdivided into 2 groups: i) B. spicifera isolates which were substantially smaller, had less septation, and were considerably different from B. sorokiniana spores ( Kumar et al, 2002 ; Kachkouch et al, 2011 ; Qostal et al, 2019 ); and ii) E. rostratum isolates with long, thin spores with thick, dark-colored septa at both ends and were very different from the other 2 groups ( Ahmadpour et al, 2013 ; Bunkoed et al, 2014 ; Sharma et al, 2014 ; Hernández-Restrepo et al, 2018 ; Dhara et al, 2020 ). Further, molecular identification with ITS and GAPDH region sequencing revealed the presence of another pathogenic group, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Later, based on spore morphology and sporulation studies, group I isolates were identified as B. sorokiniana isolates with olive green to brown oblong conidia with prominent scar at the base, having dimensions in the range of 60–120 μm × 15–20 μm and 3–9 septa ( Aggarwal et al, 2009 ; Acharya et al, 2011 ; Devi et al, 2021 ). Group II isolates were further subdivided into 2 groups: i) B. spicifera isolates which were substantially smaller, had less septation, and were considerably different from B. sorokiniana spores ( Kumar et al, 2002 ; Kachkouch et al, 2011 ; Qostal et al, 2019 ); and ii) E. rostratum isolates with long, thin spores with thick, dark-colored septa at both ends and were very different from the other 2 groups ( Ahmadpour et al, 2013 ; Bunkoed et al, 2014 ; Sharma et al, 2014 ; Hernández-Restrepo et al, 2018 ; Dhara et al, 2020 ). Further, molecular identification with ITS and GAPDH region sequencing revealed the presence of another pathogenic group, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(i) bacteria such as Achromobacter and Nectria in Nave high, Hirschia in Bulls wall, Aliihoeflea and Arenibacter in Bulls left, which may produce pigments [ 68 71 ], and (ii) Fungi e.g. Bipolaris, Xylodon and Itersonilia pointed in the Apse [ 22 ] and known for yellow–brown pigment production [ 72 ].…”
Section: Discussionmentioning
confidence: 99%